2007
DOI: 10.1007/s11373-007-9189-8
|View full text |Cite
|
Sign up to set email alerts
|

Knock down of gfp and no tail expression in zebrafish embryo by in vivo-transcribed short hairpin RNA with T7 plasmid system

Abstract: SummaryA short-hairpin RNA (shRNA) expression system, based on T7 RNA polymerase (T7RP) directed transcription machinery, has been developed and used to generate a knock down effect in zebrafish embryos by targeting green fluorescent protein (gfp) and no tail (ntl) mRNA. The vector pCMVT7R harboring T7RP driven by CMV promoter was introduced into zebrafish embryos and the germline transmitted transgenic individuals were screened out for subsequent RNAi application. The shRNA transcription vectors pT7shRNA were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…50 The use of plasmid-based shRNA for gene suppression has been successfully applied in a variety of mammalian cell systems, [51][52][53][54] and T7RNAp-driven shRNAs have been reported for the regulation of gene expression in live mammalian cells 55,56 and zebrafish embryos. 57 Here, we coupled our developed photochemical gene regulation system with an Eg5 shRNA component as a proof of principle study in the photochemical regulation of RNA interference. The Eg5 gene encodes a motor protein involved in mitosis 58 and inhibition of Eg5 with siRNA oligonucleotides has been shown to produce binucleated cells, 59,60 providing a distinct phenotypic readout for RNAi activity.…”
Section: Resultsmentioning
confidence: 99%
“…50 The use of plasmid-based shRNA for gene suppression has been successfully applied in a variety of mammalian cell systems, [51][52][53][54] and T7RNAp-driven shRNAs have been reported for the regulation of gene expression in live mammalian cells 55,56 and zebrafish embryos. 57 Here, we coupled our developed photochemical gene regulation system with an Eg5 shRNA component as a proof of principle study in the photochemical regulation of RNA interference. The Eg5 gene encodes a motor protein involved in mitosis 58 and inhibition of Eg5 with siRNA oligonucleotides has been shown to produce binucleated cells, 59,60 providing a distinct phenotypic readout for RNAi activity.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that RNA interference is a powerful tool for studying gene functions and exploring gene regulatory mechanisms [21][22][23][24] . In addition, previous studies have reported that hydrodynamic intravenous injection via tail vein is an effective method for the delivery of shRNAs to the hepatocytes in vivo [25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…shRNAs appear to circumvent the toxicity caused by microinjection of double-stranded RNAs or siRNAs, at least when expressed through microinjected plasmids. Constitutive shRNA expression through the use of U635 or CMV36 promoters induced a modest knockdown of GFP, Ntla, and VEGF-A protein levels at plasmid doses that did not cause toxic off-target effects 37. Driving shRNA expression through a hybrid U6/CMV promoter can enhance RNA interference efficiency, reducing Ntla protein to approximately 20% of wildtype levels and producing a ntla mutant phenotype in about half of the injected embryos 38.…”
Section: Oligonucleotide Tools For Regulating Rna Functionmentioning
confidence: 99%